The world beyond the northern margin: the Bronze Age Aegean and the east Adriatic coast - Tomas, Helena (2010)
The paper discussed traces of contacts between the Aegean area and the east Adriatic coast during the Bronze Age. It addresses the latter in the context of the world system theory.
Projekt MZOS
ENG